Curcumin adsorption on carbon microparticles: Synthesis from soursop (annonamuricata l.) peel waste, adsorption isotherms and thermodynamic and adsorption mechanism - Nandiyanto, A.B.D. (Universiti Malaysia Perlis, 2020)
The aims of this study was to evaluate adsorption isotherm of carbon microparticles prepared from calcination of soursop (Annona Muricata L.) peel waste (at temperature of 250Â°C). Adsorption test was done by mixing the prepared carbon microparticles (with sizes of 74, 250, and 500 Âµm) and curcumin (extracted from Indonesian local turmeric) in an aqueous solution at a constant pH, room temperature and pressure, and in the batch-typed adsorption reactor. Experimental results were then compared with the standard isotherm models, i.e., Langmuir, Temkin, Freundlich, Dubinin-Radushkevich, Flory-Huggins, Fowlerâ Guggenheim, and Hill-de Boer adsorption models. The results showed that particle size is very important to predict the adsorption process, therefore it is very important to have a homogeneous particle distribution (size and shape) to determine the adsorption properties. The data of regression value from the adsorption analysis indicated that the best fit isotherm models sequentially followed Hill-de Boer > Fowler > Flory > Temkin> Langmuir > Dubinin-Radushkevich > Freundlich. The adsorption process takes place on a multilayer surface, and the adsorbent-adsorbate interaction is a physical adsorption (which confirmed and is good agreement with the results from Hill-de Boer models and suitable with Freundlich, Temkin, and Dubinin-Radushkevich). Adsorption is carried out at different locations energetically under endothermic processes. The Gibbs free energy calculated is negative for all models, informing that the adsorption process is done spontaneously. This study demonstrates the useful process for producing carbon microparticles from soursop peel, giving good alternative for further development of carbon material from domestic waste. Â© 2020, Universiti Malaysia Perlis. All rights reserved.